Vivências em tempos de pandemia e seus impactos na saúde mental - Brito, Carolina Augusta Romão de (Universidade Federal de São Carlos, 2023)
The following work aims the constructi on of a review about mental health concepts, COVID-19 pandemics, and it´s development, as well as its impact in mental health. Besides, following the Political and Educational Project of the medical course, I report my own experience during medical graduati on at UFSCar, as well as medical student long pandemic.
Experiences in times of pandemic and their mental health impacts
Keywords: Saúde mental; Pandemia; Covid-19; CIENCIAS DA SAUDE::MEDICINA